2012
DOI: 10.1186/1471-244x-12-78
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion lifestyle interventions for weight management in psychosis: a systematic review and meta-analysis of randomised controlled trials

Abstract: BackgroundPsychiatric patients have more physical health problems and much shorter life expectancies compared to the general population, due primarily to premature cardiovascular disease. A multi-causal model which includes a higher prevalence of risk factors has provided a valid explanation. It takes into consideration not only risks such as gender, age, and family history that are inherently non-modifiable, but also those such as obesity, smoking, diabetes, hypertension, and dyslipidemia that are modifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 41 publications
(104 reference statements)
3
118
1
11
Order By: Relevance
“…In a meta-analysis on randomised, controlled, cognitive-behavioural weight loss trials, Bonfioli et al (2012) concluded that in patients with psychosis, a weight loss of 0.98 points in BMI (corresponding to a loss of 3.12% of initial weight) was demonstrated from pooled data. Weight loss programs can also prevent weight gain associated with antipsychotic use and even promote weight loss (Chen et al, 2009, Gabriele et al, 2009, Menza et al, 2004, Vreeland et al, 2003.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In a meta-analysis on randomised, controlled, cognitive-behavioural weight loss trials, Bonfioli et al (2012) concluded that in patients with psychosis, a weight loss of 0.98 points in BMI (corresponding to a loss of 3.12% of initial weight) was demonstrated from pooled data. Weight loss programs can also prevent weight gain associated with antipsychotic use and even promote weight loss (Chen et al, 2009, Gabriele et al, 2009, Menza et al, 2004, Vreeland et al, 2003.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The most important result was the improvement of HRQoL demonstrated by the EQ-VAS within the intervention group. Previous research has shown that interventions based on group activities are efficient (Green et al, 2014, Bonfioli, et al, 2012, Verhaeghe et al, 2011, Happel et al, 2012, and that QoL is shown to be one of the variables most affected by interventions (Happel et al, 2012). Our intervention attempted to take a multifaceted grasp of lifestyle, here defined as physical activities, and education in lifestyle and nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Pearsall et al, 2014, Bonfioli et al, 2012, Happell et al, 2012, Papanastasiou, 2012, Lowe and Lubos, 2008 have demonstrated a great variety of lifestyle interventions for persons with psychosis. In the absence of convincing research findings, there is no consensus or "golden standard" of lifestyle interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of such medicines for many people is secondary to inherited cardiovascular risk (Phutane et al, 2011;Chang and Lu, 2012) and the impact of an unhealthy lifestyle (Benseñor et al, 2012) suggesting that the delivery of nutritional behaviour change interventions could have a positive impact on health. Systematic reviews of lifestyle interventions have shown some promising outcomes in people with serious mental health problems (Caemmerer et al, 2012;Bonfioli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%